Adrenal Crisis Simulation - Miriam Kulkarni; Karma Warren (Association of American Medical Colleges, 2015)
Abstract Introduction Adrenal crisis is a life-threatening emergency requiring immediate treatment with glucocorticoids to avoid morbidity and mortality. The clinical presentation of adrenal crisis is nonspecific and can mimic many other conditions. Simulation can help prepare learners to recognize and treat this emergent condition. This resource is a simulation of a patient who presents to the emergency department with hypotension that is not improved with IV fluids and pressors. Careful history taking will elucidate the fact that the patient has a history of sarcoid and has abruptly stopped his chronic steroids. Methods The scenario is designed to be used with SimMan. The parts of EMS personnel, the patient's wife, nurse, and intensive care unit fellow are played by actors. During the session, residents need to recognize that the patient is ill, recognize hypotension, perform a focused history and physical, and initiate appropriate treatment and follow-up. Results This simulation has been used as a teaching case for a group of eight PGY3 and PGY4 emergency medicine residents as part of a didactic module on endocrine emergencies. Four of the residents were active participants in the scenario, while the other four observed and provided feedback. The residents involved did not make the diagnosis until they were prompted to obtain additional history. They were able to recognize adrenal crisis and successfully completed the case. During the case and the debriefing afterward, there was lively discussion of the differential diagnosis of the patient's hypotension and the appropriate next step in the workup. Discussion If the case is to be used for junior residents or medical students, the instructors should consider modifying it to feature a patient with autoimmune Addison's disease who has stopped taking his steroids. The patient may wear a bracelet that indicates glucocorticoid dependence. If the instructors choose to change the case to primary adrenal insufficiency, the labs should be modified. The patient should be hyperkalemic, hyponatremic, and hypochloremic. The confederate nurse should point out that the patient is hyperpigmented.